2017
DOI: 10.3389/fevo.2017.00103
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensionality of Modification in an Isopod-Acanthocephalan System

Abstract: The acanthocephalan parasite Acanthocephalus dirus infects the freshwater isopod Caecidotea intermedius as an intermediate host before completing its life cycle in a fish. Transmission to the definitive host occurs after the parasite has reached the cystacanth stage and development into this stage is associated with changes in several behavioral and physiological traits of the host. Despite the numerous examples of trait modification in this system, little is known about the multidimensional nature of this mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 95 publications
(176 reference statements)
0
2
0
Order By: Relevance
“…Recent studies showed that behavioural plasticity (individual differences in behaviour) and consistency (consistent among-individual variation in behaviour) of intermediate hosts differed among both host sex and infection status (Park and Sparkes, 2017 ). Unfortunately, we were unable to test sex-specific behaviour of amphipods in our study, because we did not have the time to identify the sexes of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that behavioural plasticity (individual differences in behaviour) and consistency (consistent among-individual variation in behaviour) of intermediate hosts differed among both host sex and infection status (Park and Sparkes, 2017 ). Unfortunately, we were unable to test sex-specific behaviour of amphipods in our study, because we did not have the time to identify the sexes of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to indirect-lifecycle parasites, direct-lifecycle parasites would benefit by enhancing rather than decreasing the survival of the definitive host in which they live (Phillips, 2012). Multidimensional manipulation of host behavior in such a system is likely to be subtle; for example, parasite fitness might be enhanced by causing an infected host to become gregarious (thereby increasing rates of transmission) or to select habitats that enhance rates of survival or transmission of parasite larvae (Park & Sparkes, 2017;Perrot-Minnot, Maddaleno, Balourdet, & Cézilly, 2012;Thomas et al, 2010).…”
mentioning
confidence: 99%